Pengaruh Reputasi Kantor Akuntan Publik, Manajemen Risiko, Pengendalian, dan Kinerja Keuangan terhadap Harga Saham - Santoso, Nathalia; Setiawan, Amelia; Djajadikerta, Hamfri; Wirawan, Samuel (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The rapid growth of stock investment applications is encouraging people to enter the world of investment. Supported by the ease of using applications that are much simpler compared to offline methods in the past. The widespread use of investment applications has led to cases of speculative stocks, resulting in tens of trillions in losses. Researchers are interested in finding a solution to this phenomenon by examining the determining factors of stock prices through testing the influence of the reputation of public accounting firms, disclosure of Enterprise Risk Management (ERM), disclosure of Internal Control (IC), and financial performance on stock prices in banking companies listed on the Indonesia Stock Exchange from 2016 to 2021. The research methods used include t-test, f-test, coefficient of determination test, and multiple linear regression analysis. Based on the research results, the reputation of public accounting firms, disclosure of Enterprise Risk Management (ERM), and financial performance partially influence the stock prices of banking companies listed on the Indonesia Stock Exchange from 2016 to 2021. Meanwhile, the disclosure of Internal Control (IC) does not have a partial effect on the stock prices of banking companies listed on the Indonesia Stock Exchange from 2016 to 2021. However, all four variables have a simultaneous effect on the stock prices of banking companies listed on the Indonesia Stock Exchange from 2016 to 2021.